PENGGUNAAN TEKNOLOGI VIRTUAL REALITY DALAM PENDIDIKAN KEPERAWATAN JIWA : LITERATURE REVIEW - Deborah Ferdinanda Lumenta (Politeknik Kesehatan Kemenkes Sorong, 2021)
ABSTRACT Introduction: In the era of industrial revolution 4.0, distance learning has a strategic role for spreading and equity in higher education, including nursing science. Triggered by the COVID 19 pandemic, nursing education needs to innovate how to achieve the competency without direct contact with patients. This study aimed at exploring the virtual reality method in nursing education, moreover in mental health nursing. Method: The study design is a literature review, using Pubmed as the search engine, continued with literature search from the selected articles, using the following key words: nursing education, virtual reality, competency; and nursing education, virtual reality, and mental health. We selected only English and articles of the recent 10 years Result: Eight articles were selected using the two sets of key words, consisted of 5 articles about nursing education and 3 articles were more on mental health nursing education. The study designs were varied from RCT, review and scoping review, descriptive study, and qualitative study. The context were undergraduate and postgraduate students. Conclusion: Virtual reality is one candidate in nursing education, especially in mental health nursing education to improve competency among nursing student. Keyword: nursing education; virtual reality; mental health. ABSTRAK Pendahuluan: Dalam era revolusi industri 4.0. pendidikan jarak jauh mempunyai peran strategis untuk perluasan dan pemerataan pendidikan tinggi, termasuk pendidikan keperawatan. Dipicu wabah COVID 19, pendidikan keperawatan perlu berinovasi bagaimana meningkatkan kompetensi meskipun tidak berkontak langsung dengan pasien. Studi ini bertujuan mendalami metode virtual reality (VR) dalam pendidikan keperawatan, khususnya keperawatan jiwa. Metode: Desain studi ini adalah penelusuran literatur dengan menggunakan search engine Pubmed, dilanjutkan dalam daftar pustaka pada artikel yang terpilih, menggunakan kata-kata kunci nursing education, virtual reality, competency; dan nursing education, virtual reality, and mental health. Artikel terpilih dibatasi hanya yang berbahasa Inggris dalam sepuluh tahun terakhir. Hasil: Delapan artikel terpilih dari dua set kata kunci, yang berbicara pendidikan keperawatan secara umum (5 artikel) dan keperawatan jiwa (3 artikel). Desain penelitian ke-8 artikel bervariasi, terdapat dua RCT, tiga review dan scoping review, dua studi deskriptif, dan satu studi kualitatif. Konteks penelitian ada pada mahasiswa S1 dan pendidikan lanjut. Kesimpulan: Virtual Reality adalah salah satu kandidat metode pendidikan yang berpotensi meningkatkan kompetensi mahasiswa keperawatan, khususnya di bidang keperawatan jiwa. Kata Kunci: nursing education;virtual reality;mental health